Computer games as distraction from PAIN: Effects of hardware and difficulty on pain tolerance and subjective IMMERSION. Issue 139 (July 2020) - Fairclough, Stephen H; Stamp, Kellyann; Dobbins, Chelsea; Poole, Helen M
Highlights: Pain tolerance was higher when game difficulty increased in three studies. Display hardware and audio volume had no significant influence on pain tolerance. Sympathetic activation increased with game difficulty. Increased sympathetic activation had a direct, positive effect on pain tolerance. Cognitive demand is the primary driver of increased pain tolerance during gaming. Abstract: Technology, such as computer games and virtual reality (VR), can be used to distract attention from pain. This type of non-pharmacological intervention is cost-effective, efficient and avoids complications arising from medication. However, the capacity of technology to capture attention and effectively distract from painful stimulation is determined by different factors related to the experience of immersion, such as: sensory immersion, i.e. the audio-visual presentation of the digital world, and challenge-based immersion, i.e. effortful engagement with goals in the digital world. Four studies were performed to explore the influence of both sensory and challenge-based immersion on pain tolerance using computer games in combination with the cold pressor test. Study One ( N = 30) explored sensory immersion by contrasting pain tolerance during gameplay using VR display, 2D head-mounted micro-display and flatscreen TV, but no significant effect of display type on pain tolerance was observed. Study Two ( N = 70) manipulated challenge-based immersion and reported a significant increase of pain tolerance when participants played a highly-demanding game compared to a game with low demand. Study Three ( N = 60) simultaneously manipulated sensory immersion via screen display size (40″ vs 9″) and challenge-based immersion (game demand); pain tolerance increased in a linear fashion with demand but no significant effect of display size was reported. The fourth study ( N = 40) also manipulated both forms of immersion via systematic manipulation of game music/sound volume (11.6 vs. 57.8 dB) and game demand, no effect for audio volume was observed but pain tolerance increased when the game was highly demanding. All studies included measures of cardiovascular psychophysiology and a subjective index of immersion. Analyses of the relationship between measures revealed that greater autonomic activation exerted a direct, positive effect on pain tolerance, i.e. higher activation = greater pain tolerance. It is concluded that challenge-based immersion is the primary means by which technology can distracts attention from pain.